Culture, Health care Services, Location, and Maternal Mortality in the Southern Senatorial Zone of Taraba State, Nigeria - Andeskebtso Yohanna Adaki; Wajim John (Research Synergy Foundation Press, 2025)
Maternal mortality is a persistent global health concern, and the Southern Senatorial Zone of Taraba State in Nigeria is no exception to this challenge. This study examined the determinants of maternal mortality in the Southern Senatorial District of Taraba State, Nigeria. It utilized a questionnaire-based approach involving a sample of 1218 women of childbearing age, by focusing on three primary factors: quality of healthcare services, cultural influences, and geographical location. The findings of the study revealed significant relationships between cultural factors, quality of healthcare services, and maternal mortality in Southern Senatorial District of Taraba State. Cultural factors were found as the most influential predictor of mortality, with a coefficient of 0.312 (p < 0.001), indicating a positive relationship between cultural influences and maternal mortality rates. Quality of healthcare services also showed a substantial impact, with a coefficient of -0.0123 (p < 0.001), suggesting that higher-quality healthcare services are associated with lower maternal mortality rates. Lastly, location showed a weaker but still significant influence on mortality in the study area, with a coefficient of 0.262 (p < 0.001). This highlights the importance of geographical factors in maternal health outcomes. Based on the findings, the study recommended an array of interventions, encompassing improvements in healthcare infrastructure, mitigation of socioeconomic drivers, enhancement of educational opportunities, empowerment of women, and the implementation of culturally sensitive approaches to reduce maternal mortality within the study area).